Linguistic Discrimination in an English Language Teaching Program: Voices of the Invisible Others - Vanegas Rojas, Marlon; Fernández Restrepo, Juan José; González Zapata, Yurley Andrea; Jaramillo Rodriguez, Giovany; Muñoz Cardona, Luis Fernando; Ríos Muñoz, Cristian Martín (Íkala, Revista de Lenguaje y Cultura, 2016)
This descriptive research provides insight into how linguistic discrimination influences students’ academic performance in the English teaching program at Fundación Universitaria Luis Amigó in Medellin. Five groups were observed on four different occasions to accomplish the purpose of the study. Four professors and twelve students were interviewed to find out what attitudes and beliefs emerged inside the classroom. The analysis of data showed that standard language, native-speaker idealization, pressure from the professor, disesteem of one’s own language-level, and discriminatory attitudes affected students’ performance in aspects such as socio-affective factors, fear of negative evaluation, communication apprehension, devaluation of students’ language variation, academic performance homogenization, mother-tongue restriction, extra visibility of high-proficiency students, discriminatory jokes, linguistic segregation, difficulty in interaction, and self-isolation. This study concluded that academic performance is affected by all types of discriminating attitudes, either in professors or classmates. Discriminatory attitudes trigger responses such as fear, segregation, anxiety, and apprehension, among others, thereby restraining and limiting class participation, quality of interaction, new concept and knowledge appropriation, motivation towards language, and course contents.